The distribution of estate under Islamic law in Malaysia / Mohamad Shariffudin Abd Manan - Abd Manan, Mohamad Shariffudin (Faculty of Law, 1986)
In all the States of Peninsular Malaysia (with the exception of those parts of Negeri Sembilan and Melaka where the adat perpateh is followed to the exclusion of Muslim law) the Muslim rules of inheritance of intestacy are followed. These rules are however subject to the following in the Malay States (a) On the death of a peasant his widow is entitled to a special share in his estate, as her share in harta sapencharian unless provision has been made for her inter vivos, as for example by registering land in her name. If the deceased had no children and the estate is small she may take the whole estate} in other cases she takes a half or less according to circumstances.